Role of Tobacco in Laryngeal Carcinoma (Medical Forum Monthly, 2020)
Objective: To Study the Role of Tobacco in Laryngeal Carcinoma. Study Design: Observational StudyPlace and Duration of Study: This study was conducted at the Department of ENT, Khuwaja Muhammad Saffdar Medical College, Sialkot and Sialkot Medical College, Sialkot from Jan 2016 to Jan 2020.Materials and Methods: One Hundred patients of Laryngeal Carcinoma were included in this study. Most of the patients were smokers. The history and clinical examination was taken in all of the patients. The Biopsy of all the patients of laryngeal carcinoma was also taken in these patients. The Demographic data was recorded in designed Performa. The written informed consent was considered from every sick person included in the study. The permission of Ethical committee was also taken before collection of data and get publishing in the medical journal. The results were analyzed on SPSS version 10.Results: The incidence of Laryngeal Carcinoma in Smokers was highest in age group (51- 60years) 24% and lowest in age group (71-80years) 07%. It was also observed that incidence was highest in male 88% as compare to female 12% because male has more involvement in Tobacco smoking. The smokers are urban area 54% are more prone to Laryngeal Carcinoma as compared to rural area 46%. The incidence of Laryngeal Carcinoma was highest 50% in lower class of population as compare to middle 40% and upper class 10% of people. The incidence of Laryngeal Carcinoma was highest in tobacco users 35% and lowest in cigrate+huqqa users 10% and smoking+tobacco chewing 10%.Conclusion: The conclusion was drawn from the study that most of the patients of laryngeal Carcinoma were smokers.